Numerical analysis of power system transients and dynamics - Ametani, Akihiro (London, United Kingdom The Institution of Engineering and Technology, 2015)
The book has 14 chapters and deals with the following subjects: circuit theory-based approach; numerical electromagnetic analysis; EMTP-ATP; electromagnetic transients simulation; EMTP-RV; PSCAD-EMTDC; XTAP; numerical electromagnetic analysis; FDTD method; PEEC method; lightning surges; renewable energy system components; surges; wind power plant system; protective devices; fault locator; high-speed switchgear; FACTS; voltage-sourced converter; SVC; cable systems; and grounding system transients.
Electronic reproduction.
Keywords: Transients (Electricity) -- Mathematical models; Numerical analysis; Electric fault location; Electric power distribution -- High tension -- Computer programs; Electric switchgear; Flexible AC transmission systems; Overvoltage; Transients (Electricity).; Wind power plants; Electronic books